Uji Komposisi Media Tanam dan Pemberian Pupuk Majemuk NPK pada Pembibitan Tanaman Cabai Rawit Hiyung - Muhammad Irpan; Hairu Suparto; Akhmad Rizali (Universitas Lambung Mangkurat, 2021)
Hiyung's chili is a local chili from Hiyung Village, Tapin, South Kalimantan. Hiyung's chili cultivation begins with a process nursery, nursery is one of the most important plant cultivation processes, which will determine the amount of Hiyung's chili production. This research aims to know the best composition of growing medium mixture, the best dosage compound of NPK fertilizer and the best interactions between the composition of growing medium mixture and the dosage compound of NPK fertilizer for Hiyung's chili nurseries. This research was conducted in Greenhouse the Faculty of Agroecotechnology, Lambung Mangkurat University from July - August 2020. This research use completely randomized design two factor, there are 12 treatments combination and 4 replications, totaling 48 experimental unit. Each experimental unit consists 4 polybags for a total of 192 polybags. The results showed the best composition of growing medium mixture for height of Hiyung's chili, is in the m3 treatment (150 grams of cow manure: 50 grams rice husk). The dosage compound of NPK fertilizer is in the p1 treatment (0.6 gram / plant). The best interactions between the composition of growing medium mixture and the dosage compound of NPK fertilizer for growth of leaf number plant Hiyung's chili is 150 grams of cow manure: 50 grams rice husks and 0.6 gram / plant.